‘With a Piano, Belly-Dancing is Impossible’: Representations of the Ottoman Empire in Israeli ‘Realms of Memory’ - Rotem, Noga (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2011)
Despite the Ottoman Empire’s four hundred-year rule over the ‘Land of Israel’ (Eretz Yisr’ael), its position in Jewish-lsraeli collective memory has been negligible at best, and an object of oblivion, or even denigration, at worst. This article analyzes images and representations of Ottoman rule over the ‘Land of Israel’ as articulated in four major ‘realms of memory’: preservation of Ottoman buildings, school textbooks, children’s literature, and museums. The article suggests that historical omissions of the Ottoman Empire are not the result of a ‘natural’ erosion of memory, rather, a consistent construction, embedded in three intricately linked political contexts: The Zionist incorporation of the Orientalist dichotomy of east and west; the denial of Palestinian history and nationhood; and the Zionist Movement’s self-attributed sense of primordial nationalism. The article moves on to discuss a number of new historical studies which shed light on Ottoman history in general and the Ottoman past of the State of Israel in particular. These studies, apart from their significant role in rehabilitating the Ottoman past, also demonstrate the dramatic fractures underlying the relationship between ‘history’ and ‘memory’.